Workshop on a Cross Section of Archean Crust : field guide and abstracts presented to the 1983 Archean Geochemistry--Early Crustal Genesis Field Workshop - Ashwal, Lewis D.; Card, K. D.; orcid:0000-0001-7277-9007 (Lunar and Planetary Institute, 1983)
Various topics relevant to crustal genesis, especially the relationship between Archean low - and high-grade terrains, were discussed. The central Superior Province of the Canadian Shield was studied. sponsored by Geological Survey of Canada . [and others]. edited by L.D. Ashwal and K.D. Card Is the Kapuskasing structure the site of a cryptic suture? / Burke, K. -- Ion microprobe zircon geochronology of the Uivak gneisses: Implications for the evolution of early terrestrial crust in the North Atlantic Craton / Collerson, K.D. -- Geophysical consequences of Phanerozoic and Archean crustal evolution: Evidence from crustal cross-sections / Fountain, D.M. -- Use of olivine and plagioclase saturation surfaces for the petrogenetic modeling of recrystallized basic plutonic systems / Hanson, G.N. -- Venus topography; Clue to hot-lithosphere tectonics? / McGill, G.E